OPTIMALISASI KOMUNIKASI INTERPERSONAL: MENJALIN KOMUNIKASI INSTRUKTUR DAN KLIEN DI PANTI REHABILITASI SOSIAL TUNA SOSIAL BARAKAT CANGKAL BACARI KALIMANTAN SELATAN - Apriati, Yuli; Shalihah, Shalihah (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
Interpersonal communication, as the main foundation in social interactions and relationships, plays an important role in changing individual attitudes, views and behavior. This research aims to detail the factors that support interpersonal communication between instructors and clients at the Barakat Cangkal Bacari Social Rehabilitation Home for the Impaired, South Kalimantan. In this qualitative research method, 13 informants were selected using a purposive sampling technique. Data was collected through observation, interviews and documentation, then analyzed using data reduction techniques, data presentation and drawing conclusions. To ensure the validity of the data, extended observations, increased persistence and triangulation were carried out. The research results highlight that trust, supportive attitudes, and openness are the main factors in supporting interpersonal communication. Based on these findings, it is recommended that instructors and clients continue to maintain positive interpersonal communication, while the Barakat Cangkal Bacari Social Rehabilitation Center for the Physically Impaired can increase support and motivation for clients, as well as respond quickly to problems that arise.